PEMBUATAN PERANGKAT LUNAK UNTUK PREDIKSI SIFAT TERMODINAMIKA DAN TRANSPORT CAMPURAN TERNER HIDROKARBON - Setyo Indartono, Yuli
Replacement of R-12 with hydrocarbons and R-22 mixtures is considered in this research. Additional of R-22 into hydrocarbon mixtures is aim to reduce hydrocarbon flammability. To find the proper composition between hydrocarbon and R-22, a software was developed to predict its thermodynamics and transport properties. Thermodynamics properties calculation were done by using three equation of state, ie. Redlich-Kwong, Redlich-Kwong-Soave, and Peng- Robinson. Matrices algorithm was used to implement the properties calculation. The algorithm was proofed to be faster than the previous calculation that used arithmetic algorithm. From the result and validation of the software, it was known that Redlich- Kwong-Soave and Peng-Robinson equation of state have a better accuracy. But all of the equations of state have a poor result when predicting the specific volume in the saturated liquid region. The same condition was happened in the specific heat equations that developed from each equation of state. Saturated pressure and glide temperature are two boundary conditions that were used in the process to find the best composition between hydrocarbons mixture and R-22. The pressure must be around R-12 saturated pressure, and glide temperature must be less than 12 Â°C. From the calculation, the best mixture composition (in mole fraction) is propane 0.5, iso-butane 0.4, and R-22 0.1. The maximum mole fraction of R-22 is 0.2. COP of the refrigeration system that using hydrocarbon and R-22 mixture as refrigeran was calculated. The results show that the mixture gives better COP than R-12. Hydrocarbon and R-22 mixture have a high convection heat transfer coefficient than R-12. But the latent heat is higher than R-12, and LMTD value is smaller than R-12. Thus the heat transfer area needed for hydrocarbon and R-22 mixture is larger than R- 12.